Effects of a combination treatment of KD5040 and L-dopa in a mouse model of Parkinson's disease - Sora Ahn; Taek-Jin Song; Seong-Uk Park; Songhee Jeon; Jongpil Kim; Joo-Young Oh; Jaehwan Jang; Sanhwa Hong; Min-A Song; Hye-Seoung Shin; Young-Rim Jung; Hi-Joon Park (BMC, 2017)
Abstract Background Although the dopamine precursor L-3, 4-dihydroxyphenylalanine ( l -dopa) remains the gold standard pharmacological therapy for patients with Parkinson's disease (PD), long-term treatment with this drug has been known to result in several adverse effects, including l -dopa-induced dyskinesia (LID). Recently, our group reported that KD5040, a modified herbal remedy, had neuroprotective effects in both in vitro and in vivo models of PD. Thus, the present study investigated whether KD5040 would have synergistic effects with l -dopa and antidyskinetic effects caused by l -dopa as well. Methods The effects of KD5040 and l -dopa on motor function, expression levels of substance P (SP) and enkephalin (ENK) in the basal ganglia, and glutamate content in the motor cortex were assessed using behavioral assays, immunohistochemistry, Western blot analyses, and liquid chromatography tandem mass spectrometry in a mouse model of PD induced by 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP). In addition, the antidyskinetic effects of KD5040 on pathological movements triggered by l -dopa were investigated by testing abnormal involuntary movements (AIMs) and measuring the activations of FosB, cAMP-dependent phosphor protein of 32 kDa (DARPP-32), extracellular signal-regulated kinases (ERK), and cAMP response element-binding (CREB) protein in the striatum. Results KD5040 synergistically improved the motor function when low-dose l -dopa (LL) was co-administered. In addition, it significantly reversed MPTP-induced lowering of SP, improved ENK levels in the basal ganglia, and ameliorated abnormal reduction in glutamate content in the motor cortex. Furthermore, KD5040 significantly lowered AIMs and controlled abnormal levels of striatal FosB, pDARPP-32, pERK, and pCREB induced by high-dose l -dopa. Conclusions KD5040 lowered the effective dose of l -dopa and alleviated LID. These findings suggest that KD5040 may be used as an adjunct therapy to enhance the efficacy of l -dopa and alleviate its adverse effects in patients with PD.